PENYULUHAN PENGGUNAAN JAMU BERAS KENCUR SEBAGAI TERAPI TRADISIONAL MENGURANGI AFTERPAIN PADA IBU POSTPARTUM DI PUSKESMAS TINGGI RAJA - Devina; Nurmasitoh; Solihin, Affan (Cattleya Darmaya Fortuna, 2025)
The postpartum period is a critical recovery phase for mothers after childbirth, often accompanied by complaints of afterpain caused by continued uterine contractions. One culturally rooted and safe alternative for pain management is the use of traditional therapies such as jamu beras kencur (a traditional Indonesian herbal drink made from rice and aromatic ginger). This community service activity aimed to increase the knowledge and awareness of postpartum mothers regarding the benefits of jamu beras kencur as a non-pharmacological therapy to reduce afterpain. The methods used included health education, interactive discussions, and demonstrations involving 20 postpartum mothers in the working area of the Tinggi Raja Community Health Center. Evaluation was conducted using pre-test and post-test questionnaires to assess participants' knowledge before and after the educational session. The results showed a significant improvement in understanding, with 80% of participants demonstrating increased knowledge as evidenced by higher post-test scores. This activity indicates that education and the promotion of jamu beras kencur as a traditional therapy are effective in enhancing community awareness and can serve as a viable promotive and preventive approach in primary healthcare settings.